2017
DOI: 10.1007/s00253-017-8172-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of Saccharomyces cerevisiae for 2,3-butanediol production

Abstract: Saccharomyces cerevisiae is a work horse for production of valuable biofuels and biochemicals including 2,3-butanediol (2,3-BDO), a platform chemical with wide industrial applications for synthetic rubber, biosolvents and food additives. Recently, a cutting-edge technology of metabolic engineering has enabled S. cerevisiae to produce 2,3-BDO with high yield and productivity. These include (i) amplification of the 2,3-BDO biosynthetic pathway, (ii) redirection of carbon flux from ethanol or glycerol toward 2,3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…Nevertheless, novel strains capable of producing high concentrations of 2,3-BD using low-cost carbon sources with minimal production of by-products are highly desirable [219]. After high-throughput screening for safe efficient microorganisms able to produce 2,3-BD [220], metabolic engineering can be applied [221,222]. Finally, genetic modifications have been performed for improvement of 2,3-BD productivity and yield, elimination of byproducts synthesis, enhancement of the ability to utilize complex substrates (most preferably without pretreatment) and resistance to environmental stresses [223,224].…”
Section: Chemicals From Hemicellulosementioning
confidence: 99%
“…Nevertheless, novel strains capable of producing high concentrations of 2,3-BD using low-cost carbon sources with minimal production of by-products are highly desirable [219]. After high-throughput screening for safe efficient microorganisms able to produce 2,3-BD [220], metabolic engineering can be applied [221,222]. Finally, genetic modifications have been performed for improvement of 2,3-BD productivity and yield, elimination of byproducts synthesis, enhancement of the ability to utilize complex substrates (most preferably without pretreatment) and resistance to environmental stresses [223,224].…”
Section: Chemicals From Hemicellulosementioning
confidence: 99%
“…2,3-BDO can be directly used as an anti-freeze agent or chemically converted to other chemicals (Fig. 1 d) [ 10 , 12 ]. For example, 1,3-butadiene (1,3-BD) can be produced by the two-step dehydration of 2,3-BDO [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an example of a case study to demonstrate this premise, previous exploration of 2,3‐butanediol (BDO) production identified that disruptions to ADH1‐5 and GPD1‐2 genes controlling ethanol and glycerol production (respectively) greatly enhanced BDO production. This rewiring is due to the removal of NADH sinks in the cell, forcing flux from acetoin to BDO through the NADH‐dependent BDH1 enzyme (Figure A). To implement this approach, researchers needed to modulate these major NADH consuming pathways simultaneously.…”
Section: Resultsmentioning
confidence: 99%